Focus on marijuana - Zeller, Paula Klevan (Frederick, MD. Twenty-first Century Books, 1990)
Describes the history, effects, social aspects, and physical dangers of using marihuana.
Keywords: Marijuana -- Juvenile literature; Marijuana -- Juvenile literature. -- United States